2005
DOI: 10.1002/chir.20196
|View full text |Cite
|
Sign up to set email alerts
|

Improved catalytic activity of homochiral dimeric cobalt–salen complex in hydrolytic kinetic resolution of terminal racemic epoxides

Abstract: Enantiomerically pure epoxides (99%, ee) and diols (98%, ee) from racemic epichlorohydrin, 1,2-epoxypropane, 1,2-epoxyhexane, 1,2-epoxyoctane, and 1,2-epoxydodecane were obtained in 2-12 h by hydrolytic kinetic resolution (HKR) using the recyclable dimeric homochiral Co(III)-salen complex 1' (0.2 mol %) derived from 5,5-(2',2'-dimethylpropane)-di-[(R,R)-{N-(3-tert-butylsalicylidine)-N'-(3',5'-di-tert-butylsalicylidine)}-1,2-cyclohexanediamine] with cobalt(II) acetate. Unlike its monomeric version, the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Separation of the catalyst is also important for its reuse as chiral catalysts are expensive. To deal with these issues, the authors have reported [6,11] dimeric forms of the Jacobsen's catalysts 3, 4. Due to the higher molecular weight, these complexes were less soluble in the reaction medium than their monomeric counterparts, hence could be easily precipitated out with the use of n-hexane in a post-catalytic work-up procedure.…”
Section: Hydrolytic Kinetic Resolution (Hkr) Of Racemic Epoxidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Separation of the catalyst is also important for its reuse as chiral catalysts are expensive. To deal with these issues, the authors have reported [6,11] dimeric forms of the Jacobsen's catalysts 3, 4. Due to the higher molecular weight, these complexes were less soluble in the reaction medium than their monomeric counterparts, hence could be easily precipitated out with the use of n-hexane in a post-catalytic work-up procedure.…”
Section: Hydrolytic Kinetic Resolution (Hkr) Of Racemic Epoxidesmentioning
confidence: 97%
“…Hydrolytic kinetic resolution of racemic epoxides is an attractive strategy for the synthesis of valuable enantiopure terminal epoxides and corresponding diols in a single step [6]. Easy availability of inexpensive terminal epoxides and the use of water as the sole reagent with a recoverable chiral catalyst makes this solvent free protocol very attractive for its commercial exploitation [7,8].…”
Section: Hydrolytic Kinetic Resolution (Hkr) Of Racemic Epoxidesmentioning
confidence: 99%
“…Nevertheless, Dioos and Jacobs have recently reported the asymmetric ring opening of epoxides using TMSN 3 as nucleophile under MW irradiation. 40 In continuation of our ongoing research toward developing the recyclable chiral dimeric and polymeric catalysts with different metal ions for various organic transformations, namely asymmetric epoxidation, [41][42][43] cyanation, 44,45 hydrolytic kinetic resolution, 46 oxidative kinetic resolution, and asymmetric ring opening of meso and trans epoxides with anilines, 49,50 in the present study we are reporting the use of recyclable dimeric and polymeric chiral Cr(III)X salen complexes 1 and 2 as catalysts for the production of enantioselective trans 1,2 aminoalcohols through AKR of racemic trans-stilbene oxide and trans-b-methyl styrene oxide, with anilines under MW irradiation as an alternate source of energy to step up the reaction rate. Significantly, the rate of reactions was greatly enhanced and there was no loss in enantioselectivity under MW irradiation in comparison to the same reaction when conducted at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many efforts have been made to develop recyclable catalysts by supporting catalytically active chiral metal complexes on to organic or inorganic supports 34,35 and ionic liquids. 36,37 There has been continued efforts by us for developing recyclable chiral catalysts for various organic transformations such as asymmetric addition of cyanide to the various aldehydes, [38][39][40] asymmetric epoxidation, [41][42][43][44][45][46] hydrokinetic resolution, 47 aminolytic kinetic resolution, 48 oxidative kinetic resolution, 49,50 and addition of phenylacetylene to carbonyl compounds. 51 Here, we are extending the application of dimeric and polymeric Mn(III) salen complexes for asymmetric addition of trimethylsilyl cyanide (TMSCN) to various ketones at room temperature.…”
Section: Introductionmentioning
confidence: 99%